1980
DOI: 10.1159/000145179
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the afferent innervation of the cricothyroid muscle in dogs

Abstract: The cricothyroid muscle in dogs received branches from two independent nerves, namely the external ramus of the cranial laryngeal nerve and the pharyngeal branch of the vagus. Classical spindles are infrequent in the muscle. Atypical forms of sensory endings were identified. Two end-plates were frequently met with on a single extrafusal fibre. Sectioning of the external ramus of the cranial laryngeal nerve was followed by degeneration of spindles. Intact axons detected up to 6 months after operation are probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The abundance of ganglia and isolated ganglion cells, respectively, within the intermuscular connective tissue and chorion of the mucosa as well as along single nerve fibers confirms the finding of Ibrahim et al [1980]. Their functional significance remains obscure.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The abundance of ganglia and isolated ganglion cells, respectively, within the intermuscular connective tissue and chorion of the mucosa as well as along single nerve fibers confirms the finding of Ibrahim et al [1980]. Their functional significance remains obscure.…”
Section: Discussionsupporting
confidence: 72%
“…The same was earlier described in the cat [Manolov et al, 1965], dog [Ibrahim et al, 1980], human [Rudolph, 1960;Kupfer, 1960], and some domestic animals [Veg getti and Mascarello, 1979]. Such a multiple or poly synaptic innervation of muscle fibers serves, in our opin ion, specific functional needs, at least in nature: (a) to determine a faster and stronger answer by a larger neurotransmitter contribution in several areas of the same muscle fiber as sustained by Hunt and Kuffler [1954], Rudolph [1960], andAbo El-Enene [1975] and (b) to obtain a fast contraction even by slow-tonic mus cle fibers, as postulated by Yellin [1969], Very long, complex or 'en grappe' neuroterminals have been described in M. quadratus of the upper lip of the rabbit [Bowden and Mahran, 1956], within the mimic musculature of cat.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Considerable controversy has continued over whether there are spindles in the laryngeal muscles. The most recent findings suggest that spindles occur only in the interarytenoid muscle and are sparse or absent in the TA, LCA, CT and PCA muscles (Ibrahim et al, 1980;Brandon et al, 2003;Tellis et al, 2004). No studies to date have demonstrated a physiological effect of muscle stretch in the human larynx.…”
Section: The Role Of Sensory Feedback In Laryngeal Controlmentioning
confidence: 99%
“…It cannot be determined if these muscle responses represented a compensatory pitch shift response to the audible pitch lowering with force application (Burnett and Larson, 2002) or stretch responses in either the sternothyroid or CT muscles. The possibility of a CT muscle stretch response is less likely given the paucity of muscle spindles in that muscle (Ibrahim et al, 1980). Many authors have hypothesized that stretch reflexes in the laryngeal muscles might provide pro-prioceptive feedback for voice control (Kirchner and Wyke, 1965;Abo-El-Enein and Wyke, 1966;Wyke, 1974).…”
Section: The Role Of Sensory Feedback In Laryngeal Controlmentioning
confidence: 99%